Leadership and management in elite sport: factors perceived to influence performance - Arnold, R.; Fletcher, D.; Anderson, R.; McKenna, J.; Vella, S. (International Journal of Sports Science and Coaching, 2015)
Extant sport psychology and sport management research has examined the factors influencing Olympic performance at the athletic and coaching, and governmental and policy levels respectively. In contrast to this abundance of literature, far less is known about the factors perceived to influence performance at the leadership and managerial level. The purpose of this study, therefore, was to investigate the factors that national performance directors (NPDs) operating at this level perceive to influence their role delivery and performance. Fourteen NPDs of Olympic sports were interviewed and data analysis revealed two general dimensions suggested to influence outcomes. The two dimensions were: self-related factors (i.e., personality, health, skills, experience) and environment-related factors (i.e., development opportunities, operations, personnel). Recommendations are provided for applied practitioners to help them raise awareness of and address the identified factors to not only enhance a NPD`s performance, but also, ultimately, that of Olympic athletes and sport organizations.